Figuration as Participation. Notes on Álvaro Siza's Architecture as Representation - Colonnese, Fabio (Enquiry The ARCC Journal for Architectural Research, 2018)
Although in the wake of the Modern Movement tradition, Álvaro Siza Vieira's architectural research moves along the thin red line between abstraction and representation. The apparent arbitrariness of some of his compositions, widely analyzed in typological and social key, is primarily an expression of his attention to the moving subject that never translates into illusory devices. Yet, in the last two decades of the 20th century, anthropomorphic and zoomorphic presences began to haunt his architectures, addressing to new meanings. The keys to understanding this phase of Siza's creative trajectory reside in his hypertrophic graphic activity, in his production as a designer and, most of all, as a sculptor. On one hand, his sketches reveal the tension and negotiation between architecture body and human body, which to some extent constitute the extremes of his formal investigation. On the other hand, his objects and sculptures result as intermediate moments of experimentation and clarification by responding the ergonomic demands through the semantic economy of objet trouvée. Through them, Siza's architectural anthropomorphism can be interpreted as a moment of transition towards an architecture parlant, which relies on the connotative participation of people to put in scene no longer figures or characters but interactions and feelings: the opportunity of a meeting.